2021
DOI: 10.1089/gyn.2021.0041
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative Genitourinary Injuries During a Hysterectomy: Risks, Management, and Mitigation Strategies

Abstract: Surgical removal of the uterus is one of the most performed procedures in women, with >600,000 hysterectomies performed per year in the United States alone, most for benign indications. Over the past decade, laparoscopy has become the more popular approach for completion of the hysterectomy globally. The increased uptake of minimally invasive approaches played a role in the adoption of outpatient hysterectomy with estimated volume ranging between 200,000 and 300,000 cases per year. And with more surgeries done… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…UI most often results iatrogenically from surgical procedures. Hysterectomy, as in our case, accounts for >50% of iatrogenic UI cases, with incidence rates estimated at 0.03–1.5% [16] , [17] , [18] . Failure to recognize UI intraoperatively, as occurred in our case, has been reported at rates of 60–90%, with considerable implications for patient outcomes [19] .…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…UI most often results iatrogenically from surgical procedures. Hysterectomy, as in our case, accounts for >50% of iatrogenic UI cases, with incidence rates estimated at 0.03–1.5% [16] , [17] , [18] . Failure to recognize UI intraoperatively, as occurred in our case, has been reported at rates of 60–90%, with considerable implications for patient outcomes [19] .…”
Section: Discussionmentioning
confidence: 83%
“…Delayed UI detection is associated with significantly higher rates of 90-d readmission, sepsis, urinary fistula, acute renal injury, and death [19] , [21] . Furthermore, postoperative UI detection typically requires temporary urinary diversion and multiple procedures or operations for definitive management, which has a considerable negative impact on patient mental health, patient-partner relationships, employment, litigation, and health care costs [17] , [20] , [21] .…”
Section: Discussionmentioning
confidence: 99%
“…Several risk factors for urinary tract injury during TLH have been reported, including a history of abdominal surgery, cesarean section, endometriosis, intra‐abdominal adhesions, broad ligament fibroids, pelvic malignancy, and pelvic radiation and a surgeon with limited surgical experience (<10 operations/year) 8 . By contrast, Chan et al suggested that congenital abnormalities, such as ureteral duplication, megaureter, and ectopic ureter or kidney, are risk factors for ureteral injury due to anatomical changes distorting the position of the ureters 9 .…”
Section: Discussionmentioning
confidence: 99%
“…(4) Although rare, major complications such as hemorrhage, bowel or urinary tract injuries and vaginal cuff dehiscence still arise and often require additional surgical or pharmacological interventions, resulting in higher morbidity and mortality risks. (5)(6)(7) Risk factors for complications include multiple surgeon and center-specific factors. Surgeon volume has repeatedly been found to be a predictive factor, as surgeries performed by high-volume surgeons are usually associated with shorter hospitalizations, fewer perioperative complications, and fewer conversions to laparotomy.…”
Section: Introductionmentioning
confidence: 99%